Co-occurrence of VHL and SDHA Pathogenic Variants: A Case Report - Moon Ley Tung; Bharatendu Chandra; Kyle Dillahunt; Matthew D. Gosse; T. Shawn Sato; Alpa Sidhu (Frontiers in Oncology, 2022)
Von Hippel Lindau(VHL)syndrome presents with cerebellar and spinal hemangioblastomas, renal cell cancer, neuroendocrine pancreatic tumor, and pheochromocytoma and it is caused by germline mutations in the VHL gene. Pathogenic germline variants in the succinate dehydrogenase A (SDHA) gene are associated with paraganglioma and pheochromocytoma. Here we report co-occurrence of germline pathogenic variants in both VHL and SDHA genes in a patient who presented with pancreatic neuroendocrine tumor. As these genes converge on the pseudo-hypoxia signaling pathway, further studies are warranted to determine the significance of co-occurrence of these variants in relation to tumor penetrance, disease severity, treatment response and clinical outcomes in this selected group of patients.